(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The Computer based / assisted system is proposed in this paper for feature extraction of lung nodule from the simple chest X-ray image. In recent years, the image processing mechanisms are widely used in several medical areas for early detection and in deciding treatment stages, where the time and cost factor is very important to discover the disease in the patient. According to WHO -among the cancer, lung cancer is one of the most common causes of death worldwide. Therefore, early detection using diagnostic tests promises to reduce mortality from lung cancer. At present, increased work load on interpretation of digital images (X-Ray and CT) by radiologist can be a potential source of error due to fatigue in detecting subtle lesion. In this work, the problem of developing a computer based system for the extraction of maximum statistical / mathematical features from the lung X-ray image is considered. Further, these properties can be used to classify lung nodule as benign or malignant from the chest X-ray image directly.